FreePatentsOnline:Respiratory biofeedback and performance evaluation system (2005)
A positive biofeedback training system which visually displays desired respiratory parameters along with performance. Suitable respiratory airflow transducer means is used to generate and compare flow signals in real time to the physician-, technician-, or teacher - prescribed desirable performance parameters, thus providing incentives to improve patient or student performance for respiratory maneuvers under varying circumstances. The system includes estimation means to quantitate deficiencies of volumetric, flow, pressure, or timing requirements to the ideal breathing patterns. The system includes methods and a flow signal is integrated to appropriate volume signal with relation to a time base. The system provides for detecting initiation of inspiration and resetting of ideal volumetric respiration pattern; comparing real time flow and volumetric signal with ideal flow and volumetric prescribed patterns, and visually displaying both ideal and real time performance on a suitable display. This system is particularly adapted for clinic use to establish an ideal breathing pattern under various circumstances and to establish a mechanical prescription for adaptation in home use by a respiratory victim utilizing simpler device means. Appropriate performance deficiency indicators or performance enhancing indicators may be used. Appropriate performance signal recording devices and data analysis devices may be attached. The system may be further adapted for optimizing breathing device performance, breathing testing performance, and other breathing training and evaluation parameters in normal subjects training to work in unusual environments or for use with musical instrument or voice training or pregnant delivering subjects and the like. In the preferred embodiments of the invention, prescribed waveforms for inspiration flow, expiration flow, relative timing ratios of inspiration to expiration, etc. are read out of ROMs and compared with sample integrated airflow values from a RAM. A scanning beam rectilinear raster display is employed for converting digital values in real time superimposed patterns.